2016
DOI: 10.1128/iai.00445-16
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae LeuO Links the ToxR Regulon to Expression of Lipid A Remodeling Genes

Abstract: Vibrio cholerae is an intestinal pathogen that causes the diarrheal disease cholera. Colonization of the intestine depends upon the expression of genes that allow V. cholerae to overcome host barriers, including low pH, bile acids, and the innate immune system. ToxR is a major contributor to this process. ToxR is a membrane-spanning transcription factor that coordinates gene expression in response to environmental cues. In previous work we showed that ToxR upregulated leuO expression in response to bile salts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
(97 reference statements)
2
12
0
Order By: Relevance
“…Unlike V. fischeri, V. cholerae encodes an additional LPS-modifying system that confers PMB resistance: the aminoacyl lipid modifying enzymes AlmEFG. In contrast to the acid-induced modification described here, transcription of almEFG is repressed by exposure to acid via the LeuO-ToxRS-CarRS/VprAB cascade of transcription factors (Herrera et al, 2014;Ante et al, 2015;Bilecen et al, 2015;Bina et al, 2016). The V. cholerae PMB resistance phenotype is also regulated by the envelope stress response through the alternative sigma factor RpoE and the outer membrane protein OmpU (Mathur et al, 2007;Shaw, 2012).…”
Section: Discussionmentioning
confidence: 81%
“…Unlike V. fischeri, V. cholerae encodes an additional LPS-modifying system that confers PMB resistance: the aminoacyl lipid modifying enzymes AlmEFG. In contrast to the acid-induced modification described here, transcription of almEFG is repressed by exposure to acid via the LeuO-ToxRS-CarRS/VprAB cascade of transcription factors (Herrera et al, 2014;Ante et al, 2015;Bilecen et al, 2015;Bina et al, 2016). The V. cholerae PMB resistance phenotype is also regulated by the envelope stress response through the alternative sigma factor RpoE and the outer membrane protein OmpU (Mathur et al, 2007;Shaw, 2012).…”
Section: Discussionmentioning
confidence: 81%
“…). Recently, Bina and co‐workers reported that ToxR controls VprA in a LeuO‐dependent manner (Bina et al ., ). Both LeuO and ToxR are broad regulators of Vibrio pathogenicity (Shimada et al ., ; Kazi et al ., ) and deletion of either increases polymyxin resistance 3‐fold in mid‐log‐phase cells.…”
Section: Discussionmentioning
confidence: 97%
“…Among the genes that are depressed by ToxR in V. cholerae is leuO , encoding the LysR‐like wHTH DNA binding protein LeuO (Bina et al ., ). LysR‐type transcription factors (LTTRs) have very weak consensus DNA binding site sequences: T‐N 11 ‐A, where N is any base.…”
Section: Other Whth Proteins and V Cholerae And S Typhimurium Pathomentioning
confidence: 97%